2016
DOI: 10.33549/physiolres.933512
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acids, Nuclear Receptors and Cytochrome P450

Abstract: This review summarizes the importance of bile acids (BA) as important regulators of various homeostatic mechanisms with detailed focus on cytochrome P450 (CYP) enzymes. In the first part, synthesis, metabolism and circulation of BA is summarized and BA are reviewed as physiological ligands of nuclear receptors which regulate transcription of genes involved in their metabolism, transport and excretion. Notably, PXR, FXR and VDR are the most important nuclear receptors through which BA regulate transcription of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 101 publications
0
38
0
Order By: Relevance
“…The main limitation of our study is the difference in BA compositions between humans and the animal SHR model. First, HDCA does not usually exist in the human liver, but we showed that the decrease in HDCA was the major alteration in a hypertensive NAFLD rat model [10][11][12]. HCA, HDCA, alpha-MCA, beta-MCA, and omega-MCA commonly constitute the hepatic BAs in rats; however, these BAs do not usually exist in the human liver [10][11][12].…”
Section: Discussionmentioning
confidence: 87%
“…The main limitation of our study is the difference in BA compositions between humans and the animal SHR model. First, HDCA does not usually exist in the human liver, but we showed that the decrease in HDCA was the major alteration in a hypertensive NAFLD rat model [10][11][12]. HCA, HDCA, alpha-MCA, beta-MCA, and omega-MCA commonly constitute the hepatic BAs in rats; however, these BAs do not usually exist in the human liver [10][11][12].…”
Section: Discussionmentioning
confidence: 87%
“…19 The mechanism for the small reduction in C max is unclear, but bile acids (which are increased with bulevirtide) may induce organic anion transporter (OAT) 3. 20 It is unclear whether the other HBV NAs, entecavir and TAF, would be affected.…”
Section: Entry Inhibitormentioning
confidence: 99%
“…19 Increased conjugated taurine bile acids are associated with inducing CYP(3A4) and drugtransporters through stimulation of nuclear receptors. 20 As these bile acids are increased (see below) when bulevirtide is used, this could also mean that there is a DDI in vivo that is not detected in vitro. 20 Additional "cocktail" probe studies performed in vivo may shed light on the DDI potential of bulevirtide.…”
Section: Entry Inhibitormentioning
confidence: 99%
See 1 more Smart Citation
“…Type 2 diabetes mellitus (T2DM), which is characterized by impaired insulin sensitivity and progressively declining insulin secretion capacity, is a worldwide health problem . Recently, bile acids (BAs), acting through G‐protein‐coupled bile acid receptor 1 (GPBAR1; also known as TGR5) and nuclear receptors (farnesoid X receptor [FXR], pregnane X receptor [PXR] and vitamin D receptor [VDR]), have been recognized as important signals for maintaining metabolic homeostasis, and this system has been mined for novel targets for pharmaceutical intervention in metabolic disorders such as T2DM . The pleiotropic roles of BA signaling in the regulation of metabolism include reducing hepatic lipid accumulation and glucose output, promoting thermogenesis via adipose browning, and stimulating incretin and insulin secretion …”
Section: Introductionmentioning
confidence: 99%